Zagadywanie katastrofy. O literaturoznawstwie Holokaustu - Wolski, Paweł (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
The article discusses a special kind of narrative about the catastrophe, treated as a specific genre of writing: the theory of literature of the Holocaust. The article presents its two most significant (although not the only ones) features: firstly, the conviction about its unusual character as compared to other genres/forms of writing, sometimes secretly described by such concepts as the uniqueness of the Holocaust (which metonymizes not only the event itself but also the narrations referring to it) and, secondly, identifies all text-producing entities (narrator, author etc.), simultaneously constituting the basic feature of the most important genre/modality of this kind of writing which is testimony. The article presents the examples of Polish and foreign scholars portraying this state of affairs.